Characteristics of fly ash from the municipal solid waste incineration plant in Can Tho - Tra Mai, Ngo; Huu Tap, Van; Duy Hai, Nguyen; Thi Thanh Hang, Phan; Thi Tham, Trinh; Duc Toan, Vu; Thi Thuy Hang, Nguyen; Thi Hong, Khuat; Thi Ha Lien, Nghiem; Duong, Vu; Quang Hoa, Do; Trong Nghia, Nguyen; et al. (Vietnam Journal of Science and Technology, 2023)
In this study, 16 seasonal fly ash samples of municipal solid waste incinerator (MSWI) were collected in from waste-to energy power plant Cantho city to analysis the physical properties and heavy metals content. The results showed that the fly ash samples are very alkaline with porous and spherical shape, and the particle size of 1-100 µm. The analytical results disclosed that in these fly ash samples, the Zn, Pb, Al, Fe and Cr metals were found at high content range from 0.36-19.05 mg/kg while the toxic metals Ni and Hg are also found in fly ash, with the content from 0.141 to 0.51 mg/kg. Thus, fly ash is not hazardous waste and can be used for reuse in industries or land reclamation. The analysis results of SEM/EDX and XRF were quite similar with a difference of below 5%, indicating that both methods can be applied to research heavy metals. The findings in this study can guide the management, treatment and reuse of fly ash from MSWI incineration plants in Vietnam.